Current role of tribological tests: striving for full characterization of medicinal and cosmetic products - Tošić, Andjela; Stanković, Tijana; Ilić, Tanja; Savić, Snežana; Pantelić, Ivana (Archives of Pharmacy, 2023)
Tribology investigates the events that happen on the surfaces of two substances/objects that are in direct or indirect contact through assessing friction, lubrication and/or wear. In particular, friction measurements could provide the information on the textural characteristics of (per)oral pharmaceutical preparations and contribute to the understanding of palatability. On the other hand, tribological tests have been more intensively used to characterize topical preparations (pharmaceutical, cosmetic), giving a thorough insight into the tactile and texture properties of these preparations. However, these tests are often combined with rheological, textural, and certain biophysical approaches. Additionally, the materials used for constructing artificial joints and articular cartilages are true tribological systems, developed and optimized in order to have properties that resemble the natural ones. Since tribological studies can be used to assess a wide range of drug dosage forms and products in general, the equipment used may be quite diverse. Accordingly, a special section of this work is committed to the description of the testing equipment’s specifications and the applied protocols. The investigation of recently regulatory discovered phenomena, such as transformation/metamorphosis of the vehicle/base of topical preparations, have brought tribology back into focus as a potential assessment method.